Gedong Gincu mango farmer's perceptions toward the advantages and obstacles of the modern market. Issue 1 (November 2021) - Ashari,; Saliem, HP; Ariningsih, E; Suhaeti, R N; Septanti, K S; Maulana, M; De Faveri, S; Johnson, P; Shanmugam, V
Abstract: Gedong gincu mango is an exotic fruit that can become an exclusive mango to supply the modern market. This paper aims to explore the perceptions of Gedong Gincu mango farmers toward their interests, advantages, and barriers to entering the modern market. The study was conducted in Indramayu and Cirebon Districts, West Java, during Juli‒Agustus 2019, with 102 farmers as respondents. This study applied a survey method for data collection using structured questionnaires. The data were descriptively analyzed with a focus on farmer's perception of the modern market. The results showed that most respondents (>50%) in Indramayu and Cirebon Districts are interested in selling their mango to the modern market. The biggest advantages of the modern market are that they will get a higher price (75%), gain access to better quality seeds/seedlings (16.50%), and get technical assistance and new skills, especially for cultivating and handling yields (15.06%). This study also reveals factors that cause farmers reluctant to sell mangoes to the modern market. The main reason is that most farmers own small-scale farms, so they cannot meet modern market criteria (28.73%). Besides, farmers feel that the mango has low-quality products. Other farmers think they do not have the ability, experience, and sufficient information related to modern markets (14.94%). This study suggests that the government could encourage mango farmers to engage in the modern market by facilitating the training to improve farmer's capability and provide a supplier who guarantees the supply's payment and sustainability.